Association between dental pain and tooth loss with health-related quality of life: the Korea national health and nutrition examination survey. Issue 35 (August 2016) - Yang, Sung-Eun; Park, Yong-Gyu; Han, Kyungdo; Kim, Sin-Young
Abstract : Abstract: Dental pain and tooth loss are global public health concerns. However, there have been no large cross-sectional epidemiologic studies of a representative sample of an entire country's populations. The purpose of this study was to evaluate the relationships between dental pain and tooth loss with health-related quality of life (HRQOL) using a well characterized, nationally representative, population-based study. This study analyzed data of 3924, representing 21, 836, 566 adults from the 2012 Korea National Health and Nutrition Examination Survey. Subjects were divided into 4 groups as follows: tooth loss of up to 8 teeth without dental pain, tooth loss of up to 8 teeth with dental pain, tooth loss of 8 to 28 teeth without dental pain, and tooth loss of 8 to 28 teeth with dental pain. Logistic regression was applied to estimate the adjusted odds ratios (ORs) and 95% confidence intervals (CI), controlling for a range of covariates. Among the 3924 subjects, representing an estimated 21, 836, 566 adults, the prevalence of tooth loss of 8 to 28 teeth was 24.6% and the prevalence of dental pain was 35%. The tooth loss of 8 to 28 teeth with dental pain group showed the highest level of impaired HRQOL in all 5 dimensions, and the tooth loss up to 8 teeth without dental pain group showed the lowest level. The proportion of both groups without dental pain decreased significantly from the younger age to older age group. After adjustment for sociodemographic factors, the ORs (95% CI) of mobility, self-case, usual activity, pain/discomfort, and anxiety/depression were 1.93 (1.32–2.84), 1.90 (1.25–2.90), 1.46 (0.88–2.43), 1.48 (0.88–2.49), and 1.46 (0.85–2.51) in tooth loss of 8 to 28 teeth with dental pain group. Although the ORs of tooth loss of 8 to 28 teeth without dental pain group did not significantly increase. Dental pain and tooth loss has a considerable impact of HRQOL in the Korean adult population. In our study, HRQOL is more closely associated with dental pain than with tooth loss.